Pembatasan Kekuasaan Presiden dalam Pengangkatan Pejabat Strategis Negara: Perspektif Checks and Balances dalam Sistem Presidensial Indonesia - Zaenudin; Abdul Wahab (IPDN Kampus NTB, 2026)
This study aims to analyze the limits of presidential power in appointing strategic state officials from the perspective of checks and balances within Indonesia’s presidential system. The study is based on the problem that presidential authority in appointing state officials is often understood as a prerogative power, while certain strategic offices have direct implications for institutional independence, law enforcement, democratic governance, national defense, oversight of public power, and the protection of citizens’ rights. This research employs a qualitative method with a normative juridical approach. The analysis uses statutory, conceptual, and institutional case approaches to examine the appointment of constitutional justices, the Commander of the Indonesian National Armed Forces, leaders of independent institutions, ministerial officials, electoral management bodies, and acting regional heads. The findings show that presidential authority cannot be interpreted as absolute power. Its limitation must be adjusted to the nature of the office, institutional function, and risk of politicization. Pure executive offices may remain within the President’s primary discretion, while strategic offices affecting institutional independence require parliamentary control, public participation, and transparent, objective fit and proper tests. This study proposes a design for strengthening limited parliamentary oversight, meaningful public participation, and constitutionally transparent fit and proper tests. The contribution of this study lies in formulating minimum constitutional standards for appointing strategic state officials so that the presidential system remains effective without neglecting the principle of limited government.